ADULT EDUCATION AS A STRATEGY FOR "GROWING UP" DEMOCRACY: THE EXPERIENCE OF GERMANY - Volodymyr Savelʹyev; Olena Yatsenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The range of educational services is really wide. The main reasons and goals of people's universities are as follows: the formation of knowledge, the formation of beliefs, the formation of will, the formation of man. Its motivation is a return to rationalism in everyday life and "concern" for the irrational. The establishment of adult education centers is an opportunity to promote democracy. Such education forms an awareness of the political, social and cultural that can serve as the basis for a true revival of European values. The modern globalized world needs a democratic education that is not limited to national borders and the national idea. For a commonly desired future, there is a need for a broader, panoramic and forward-looking view of European values and the integrative content of European culture. Adult education centers work with traditional universities, non-governmental organizations, local associations to unite society, unite the community for a fairer and more stable social life. Such centers perform the functions of integration and translation of cultural values, universal values of humankind, teach people to be effective in the unity of diversity: uniting people of different talents, competencies and skills into an effective organism of social order.